The Effectiveness Of Destination Marketing In "Visit Malaysia 2007" Tourism Campaign - Soltani, Fatemeh (2009)
The objective of this research is threefold. The first objective is to evaluate the effectiveness of "visit Malaysia2007" tourism campaign and compare it with the number of tourist arrivals and receipts with previous years. The second objective is to assess the impat of marketing strategy in tourist arrivals and income. The third objective is to pinpoint the most vital factors of tourist satisfaction for tourists coming to Malaysia and how tourism Malaysia can benefit from them.